Influence of microstructural defects and hydrostatic pressure on water absorption in composite materials for tidal energy. (September 2018) - Grogan, DM; Flanagan, M; Walls, M; Leen, SB; Doyle, A; Harrison, NH; Mamalis, D; Goggins, J
The lifespan and economic viability of tidal energy devices are constrained, in part, by the complex degradation of the tidal turbine blade materials due to prolonged immersion in a hostile sub-sea environment. Seawater penetration is a significant degradation mechanism in composite materials. This work aims to investigate the influence of microstructure and hydrostatic pressure on water absorption in four polymer composites which are candidate materials for use in tidal energy devices. These materials are: a glass fibre powder epoxy, a carbon fibre powder epoxy, glass fibre Ampreg epoxy and a chopped fibre glass fibre Polyether Ether Ketone. X-ray computed tomography is used to characterise the voids, resin-rich areas and other manufacturing defects present in each material. These defects are known to significantly alter the rate of moisture diffusion, as well as the total uptake of water at saturation. The samples are then exposed to accelerated water aging and hydrostatic pressurisation in order to simulate a range of expected sub-sea operating conditions. The material micro-structure, the matrix material and pressurisation level are shown to strongly influence both the moisture absorption rate and total water uptake. Significant volumetric changes are also noted for all samples, both during and after aging. X-ray computed tomography scans of specimens also provide a unique insight into the role of voids in storing water once a material has reached saturation.